A experiência estética e o trabalho com valores em educação ambiental nas Salas Verdes em teses e dissertações (2000-2016) - Bueno, Silvia Lamparelli [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The goal of this study was to discuss perceptions and comprehension of authors of thesis and masters dissertations that looked into the “Green Rooms” Project” from de Ministry of Environment (MMA) projects, analyzing related environmental education practices. In order to examine those studies a state of art research, linked to a literature review, was carried out. The selected studies were conducted from 2000 to 2016 and were gathered from the EArt Project database. The analyses performed were based on the content analysis framework proposed by Bardin (2011). The focus of the analysis was to establish the perception of the research authors of the Green Room Projects studied, regarding the dimensions of Environmental Education proposed by Carvalho (1999) and the dimensions for working with values ​​in Environmental Education proposed by Bonotto (2008). The results indicate, in the authors' perceptions, emphasis on the dimensions of knowledge and values. Field activities were predominantly used to facilitate the learning of curricular contents and behaviors, views that distance themselves from the proposals of Carvalho (1999) and Bonotto (2008). Despite this, in some moments political participation was claimed, either by the authors of theses and dissertations, or by professors participating in the research, bringing local experiences to the activities.

Este trabalho teve como objetivo analisar as percepções e compreensões dos autores de teses e dissertações que olharam para os Projetos Salas Verdes analisando práticas de Educação Ambiental desenvolvidas. Para isso, foi realizada uma pesquisa de estado da arte, vinculada a revisão bibliográfica. As teses e dissertações selecionadas, entre os anos de 2000 e 2016, foram obtidas no banco do Projeto EArte. As análises realizadas foram construídas a partir do referencial de análise de conteúdo proposto por Bardin (2011). O foco das análises foi a percepção dos autores das pesquisas com relação às dimensões da Educação Ambiental propostas por Carvalho (1999) e às dimensões para o trabalho com valores em Educação Ambiental propostas por Bonotto (2008) presentes nos Projetos Salas Verdes estudados. Os resultados apontam, na percepção dos autores, ênfases nas dimensões dos conhecimentos e dos valores. As atividades de campo são utilizadas predominantemente para facilitar o aprendizado de conteúdos curriculares e de comportamentos, visões que se distanciam das propostas de Carvalho (1999) e de Bonotto (2008). Apesar disso, também foram encontrados alguns momentos em que a participação política foi reivindicada, seja pelos autores das teses e dissertações, seja por professores participantes das pesquisas que trouxeram experiências locais para as atividades.
The aesthetic experience and work with values ​​in environmental education in Green Rooms in theses and dissertations (2000-2016)
Keywords: Environmental education; Green Rooms Project; Aesthetics; Values; Educação ambiental; Valores; Estética; Projeto Salas Verdes